Cycloaddition of CO2 and epoxide catalyzed by amino- and hydroxyl-rich graphitic carbon nitride. Issue 9 (9th December 2015) - Huang, Zhijun; Li, Fengbo; Chen, Bingfeng; Yuan, Guoqing
Abstract : g-C3 N4 activated by protonation using H2 SO4 demonstrates a remarkably enhanced catalytic activity for cycloaddition of CO2 and epoxide. Abstract : Graphitic carbon nitride (g-C3 N4 ) shows great application potential in the activation of CO2 due to its basic surface functionalities and highly specific electronic properties. Herein, to improve its catalytic performance, g-C3 N4 was activated by protonation using H2 SO4 . The texture, surface chemistry and electronic properties of the as-prepared g-C3 N4 were then studied. The synthesis of cyclic carbonate from the cycloaddition of CO2 and epoxide was selected as a model reaction to investigate the catalytic performance. The protonated g-C3 N4 exhibited a much higher catalytic activity than the pristine g-C3 N4 . The generation of terminal amino and hydroxyl groups due to the hydrolysis of g-C3 N4 under acidic conditions as well as the higher specific surface area are responsible for the enhanced catalytic performance.